Clinical experiences of delayed contrast enhancement with cardiac computed tomography: case series - Sidhu Manavjot S; Ghoshhajra Brian B; Uthamalingam Shanmugam; Kilcullen Niamh; Engel Leif-Christopher; Medina Hector M; Venkatesh Vikram; Vorasettakarnkij Yongkasem; Hoffmann Udo; Cury Ricardo C; Abbara Suhny; Brady Thomas J (BMC Research Notes, 2013)
Abstract Background Myocardial delayed enhancement (MDE) by gadolinium-enhanced cardiac MRI is well established for myocardial scar assessment in ischemic and non-ischemic heart disease. The role of MDE by cardiac CT (CT-MDE) is not yet defined. Findings We reviewed all clinical cases of CT-MDE at a tertiary referral center to present the cases as a case series. All clinical cardiac CT exams which utilized CT-MDE imaging between January 1, 2005 and October 1, 2010 were collected as a series and their findings were also compared with available myocardial imaging to assess for myocardial abnormalities, including echocardiography (wall motion, morphology), cardiac MRI (delayed enhancement, morphology), SPECT MPI (perfusion defects). 5,860 clinical cardiac CT exams were performed during the study period. CT-MDE was obtained in 18 patients and was reported to be present in 9 patients. The indications for CT-MDE included ischemic and non-ischemic heart diseases. In segments positive for CT-MDE, there was excellent agreement of CT with other modalities: echocardiography (n=8) demonstrated abnormal morphology and wall motion (k=1.0 and k=0.82 respectively); prior MRI (n=2) demonstrated abnormal delayed enhancement (MR-MDE) (k=1.0); SPECT MPI (n=1) demonstrated fixed perfusion defects (k=1.0). In the subset of patients without CT-MDE, no abnormal segments were identified by echocardiography (n=8), MRI (n=1) and nuclear MPI (n=0). Conclusions CT-MDE was performed in rare clinical situations. The indications included both ischemic and non-ischemic heart disease and there was an excellent agreement between CT-MDE and abnormal myocardium by echocardiography, cardiac MRI, and nuclear MPI.